TECHNICAL INFORMATION NEEDS OF TEACHERS OF AGRICULTURAL SCIENCE ON FISHERY FOR EFFECTIVE TEACHING OF STUDENTS IN SENIOR SECONDARY SCHOOLS - , V. C, Asogwa (Innovare Journal of Education, 2016)
Abstract This study determined the technical information needs of teachers of agricultural science on fishery for effective teaching of students in senior secondary schools. Three research questions were answered for the study. The study adopted survey research design. The study was carried out in Enugu States of made up of six education zones. The population for the study was 484 teachers of agricultural science made up of 218 male and 266 in 286 registered secondary schools in Enugu State. A sample size of 145 teachers representing was proportionately randomly selected from the entire population of the teachers. A 40-structured item questionnaire titled: Fishery Teachers Technical Information Needs Questionnaire (FTINQ) was developed by the researchers from literature reviewed and used for data collection. Three experts validated the instrument. Cronbach Alpha reliability method was adopted to determine the internal consistency of the questionnaire items which produced a coefficient index of 0.89.Â  One hundred and forty-five copies of the FTINQ were administered but 138 copies were retrieved and analyzed using weighted mean to answer the research question and t-test to test the null hypotheses at .05 level of significance. It was found that teachers need technical information on 15 contents of fishery, have only 3 reliable sources of technical information to teachers on fishery and 10 constraints to accessing technical information on fishery for effective teaching of students in secondary schools. It was recommended, among others that teachers of Agricultural Science should attend seminars, workshops and conference on fishery to improve their technical information for effective teaching of students in secondary. Keywords: effective teaching, fishery, technical information, teachers of agricultural science.